Predicting Station Occupancy on Bike-Sharing System During Events: The Lisbon Case Study - Oliveira, Rita Madalena Cardoso da Silva (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence